2017
DOI: 10.1111/jir.12435
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between atypical sensory processing patterns, maladaptive behaviour and maternal stress in Spanish children with autism spectrum disorder

Abstract: The findings suggest that sensory features in ASD may be driving the high prevalence of parental stress in carers. They also suggest that the effect on parental stress that has been attributed traditionally to maladaptive behaviours may be driven by sensory difficulties. The implications of these findings are discussed in relation to the development of interventions and the need to explore contextual and cultural variables as possible sources of variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
(129 reference statements)
5
33
0
1
Order By: Relevance
“…16,17 Some research findings suggest that sensory over-responsivity is common in individuals with ASD and is linked to sleep problems, lower levels of social skills and adaptive behaviors, and increased anxiety; moreover, when combined with anxiety, it predicts an increasing level of gastrointestinal problems. [18][19][20][21] Among the few studies that included adults with ASD, the results have shown that sensory over-responsivity persists into adulthood. [22][23][24] Sensory over-responsivity can affect an individual's emotional states, education participation, social life, and work performance.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Some research findings suggest that sensory over-responsivity is common in individuals with ASD and is linked to sleep problems, lower levels of social skills and adaptive behaviors, and increased anxiety; moreover, when combined with anxiety, it predicts an increasing level of gastrointestinal problems. [18][19][20][21] Among the few studies that included adults with ASD, the results have shown that sensory over-responsivity persists into adulthood. [22][23][24] Sensory over-responsivity can affect an individual's emotional states, education participation, social life, and work performance.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory abnormalities are also core features of ASD, and have been reported to show a high prevalence in previous studies [24]. In addition, sensory abnormalities interrupt behavioral adaptation and cause behavioral problems in individual with ASD [3, 5]. Since the neural bases underlying these abnormalities have recently been receiving considerable interest from the aspect of leading to more effective diagnosis and intervention, it is important to examine the neural features corresponding to each symptom [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Other neurodevelopmental disorders typically co‐occur with tic disorders, including attention‐deficit hyperactivity disorder (ADHD), childhood‐onset obsessive‐compulsive disorder (OCD), and autism spectrum disorder (ASD). Sensory dysregulation are common in people with neurodevelopmental disorders, particularly ASD, and are associated with impaired function . Sensory dysregulation is associated with decreased school participation and engagement in daily tasks and increased parental stress levels .…”
mentioning
confidence: 99%
“…Sensory dysregulation are common in people with neurodevelopmental disorders, [24][25][26][27][28][29] particularly ASD, and are associated with impaired function. [30][31][32][33][34] Sensory dysregulation is associated with decreased school participation and engagement in daily tasks and increased parental stress levels. 17,26,30,35 Sensorimotor-based therapy is a method to manage children with autism with sensory dysregulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation